Application of peptide nucleic acids containing azobenzene self-assembled electrochemical biosensors in detecting DNA sequences - Liu, Sheng; Chen, Miao; Li, JinDu; Zhang, HaoBo; Wang, JinQing; Yang, ShengRong (Science China. Chemistry, 2009)
Hybridization of peptide nucleic acids probe containing azobenzene (NH2-TNT4, N-PNAs) with DNA was performed by covalently immobilizing of NH2-TNT4 in sequence on the 3-mercaptopropionic acid self-assembled monolayer modified gold electrode with the helps of N-(3-dimethylaminopropy1)-N’-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS), and the hybrid was coded as N-PNAs/DNA. Using [Fe(CN)6]4-/3- (1:1) as the electrochemical indicator, the electrochemical properties of the N-PNAs self-assembled monolayer (N-PNAs-SAMs) and N-PNAs/DNA hybridization system under the conditions of before and after UV light irradiation were characterized with cyclic voltammetry (CV), differential pulse voltammetry (DPV), and electrochemical impedance spectra (EIS). Results showed that the redox currents decreased with the increase of irradiation time, suggesting that the ability of the charge transfer on the electrode surface was weakened and the conformation of hybrid system had been changed, and the control of PNAs/DNA hybridization could be realized by UV light irradiation.